An Introduction to Pause and Start and their Ramifications in Arabic Syntax - Yunis Ali Yunis (دراسات في اللغة العربيّة وآدابها)
This article investigates pause, start, their ramifications and their place in syntax. This is done by probing the views expressed by the reciters and syntacticians whi have specified and justified proper locations for pause. Their reasons and justifications mainly have to do with rules of syntax and morphology, suggesting that respecting the location of pause and start requires a good knowledge of syntax and correct recitation. For example, Al Nahhas has quoted Ibn-e-Jahid as saying âonly a syntactician who knows correct recitation and is aware of the language and content of the Quran can pause and start at the right place. The article then consider the difference among the early scholars about the kinds and names of pauses. These differences reveal themselves only in the chronological order mentioned for the pauses. The idea behind the divisions is not clear and the books in this area do not agree with each other about the basis for specifying types of pauses. For locations suitable to the present discussion are defined and elaborated on: full pause, sufficient pause, appropriate pause, and rhetorical pause. The article conclude that pause and start depends on syntax and morphology and various, sometimes opposing, rules and standards govern pause and start and their types.